(untitled) (Journal of Atomic and Molecular Sciences, 2016)
Time dependent density functional theory method at the def-TZVP/B3LYP level was employed to investigate excited state intramolecular proton transfer (ESIPT) properties of 2-hydroxypyrene-1-carbaldehyde (HC). Our calculated results of the primary bond lengths and infrared vibrational spectroscopic information show that, upon photoexcitation, the intramolecular hydrogen bond is significantly strengthened in S_1 state, which facilitates the proton transfer process effectively. Furthermore, the electron density distributions of frontier molecular orbitals were demonstrated to be a positive factor for the ESIPT. By the monitor of the characteristic peaks stretching vibration of O-H group in the IR spectra, we have further confirmed the occurrence of ESIPT. The constructed potential energy surface of the S_1 state has also been used to explain the proton transfer process and evaluate the radiationless pathway, indicating that the ESIPT process occurs most easily in HC molecule.